A practical model for economic evaluation of tissue‐engineered therapies. (17th February 2015) - Tan, Tien‐En; Peh, Gary S. L.; Finkelstein, Eric A.; Mehta, Jodhbir S.
<x xml:space="preserve">Abstract</x> Tissue‐engineered therapies are being developed across virtually all fields of medicine. Some of these therapies are already in clinical use, while others are still in clinical trials or the experimental phase. Most initial studies in the evaluation of new therapies focus on demonstration of clinical efficacy. However, cost considerations or economic viability are just as important. Many tissue‐engineered therapies have failed to be impactful because of shortcomings in economic competitiveness, rather than clinical efficacy. Furthermore, such economic viability studies should be performed early in the process of development, before significant investment has been made. Cost‐minimization analysis combined with sensitivity analysis is a useful model for the economic evaluation of new tissue‐engineered therapies. The analysis can be performed early in the development process, and can provide valuable information to guide further investment and research. The utility of the model is illustrated with the practical real‐world example of tissue‐engineered constructs for corneal endothelial transplantation. WIREs Syst Biol Med 2015, 7:91–100. doi: 10.1002/wsbm.1292 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.